Exogenous Methyl Jasmonate Application Improved Physio-Biochemical Attributes, Yield, Quality, and Cadmium Tolerance in Fragrant Rice - Kanu, Adam Sheka; Ashraf, Umair; Mansaray, Lamin R.; Abbas, Farhat; Fiaz, Sajid; Amanullah, Sikandar; Charley, Christen Shaka; Tang, Xiangru (Frontiers in Plant Science, 2022)
Cadmium (Cd) has detrimental effects on crops, whereas, jasmonates (JAs) play a vital role in abiotic stress tolerance in plants. The present study investigated the effect of exogenous application of methyl jasmonate (MeJa) on physio-biochemical attributes, yield, and quality of two fragrant rice cultivars such as., Xiangyaxiangzhan and Meixiangzhan 2 under Cd stress. The experiment was comprised of four treatments i.e., Ck; control (normal conditions); Cd:100 mg Cd kg-1of soil, MeJa: exogenous application of MeJa at 20 mM, and Cd+MeJa: 100 mg Cd kg-1of soil + exogenous MeJa application at 20 mM. Results depicted that Cd toxicity resulted in a substantial reduction of enzymatic activities and non-enzymatic antioxidants, chlorophyll contents, whilst enhanced oxidative damage in terms of lipid peroxidation (higher malondialdehyde (MDA) contents), H2O2 and electrolyte leakage. Proline contents were found higher whereas protein and soluble sugars were lower under Cd stress as compared with Ck and Cd+MeJa. Exogenous MeJa application further improved the panicles per pot, spikelets per panicle, seed setting (%), 1000 grain weight, and yield per pot under Cd stress conditions as compared with non- MeJa applied plant under Cd stress. The quality attributes of both rice cultivars were also improved by MeJa application. Exogenous MeJa application improved the accumulation of macro (N, P, K, Mg, Ca) and micronutrients (Mn, Zn, Fe, and Cr) in both cultivars under Cd stress, whilst reduced the Cd contents in different plant parts. Overall, the contents of Cd in different plant organs were recorded as: root>stem>leaves>grains for all treatments. Comparing both cultivars, the grain Cd contents were higher in Meixiangzhan 2 than Xiangyaxianzhan under Cd contaminated conditions.